Knowledge and attitude of women towards the legalization of abortion in the selected town of Ethiopia: a cross sectional study - Tilahun Fufa Debela; Misgun Shewangizaw Mekuria (BMC, 2018)
Abstract Background Unsafe abortion contributes to maternal deaths 13% globally and 25-35% of Ethiopia. By considering the problem of unsafe abortion, Ethiopia amended a law that permits abortion under certain circumstances. However, the country liberalized the service, women are still not using it. Therefore, the possible reason might be a lack of knowledge and attitude is a barrier that hinders women to use safe abortion. Methods A community-based cross-sectional study was conducted in Arba Minch town from January 02 to 17, 2017. Women in the reproductive age groups (15-49) who reside in the town for more than six months were included in the study. The sample size was determined using a single population proportion formula. Five kebeles were selected using the lottery method from 11 kebeles. The proportional allocation of the sample was done for each kebeles. Data were collected using a structured questionnaire. Binary and multiple logistic analyses were carried out to identify factors associated with knowledge & attitude toward legalization of abortion. Result A total of 576 women were responded to the question. The finding of our study showed that only 23.4% of women have knowledge about the legalization of abortion. Of all the respondents 323(56%) prefer abortion on demand to be legalized while about 241 (41.9%) do not prefer to be legalized. Again about 57% of women believe that women can use it but the rest 43% believe even if allowed women do not use it. From all participants, 59% don't want to use by themselves and also, 53.3% don't think that women would have the right to use the service or terminate their pregnancy even if the pregnancy fulfill the criteria. Ethnicity, marital status, and family size were the factors significantly associated with knowledge. Again, educational status, marital status and having knowledge about the legalization of abortion were a statistically significant association with the attitude. Conclusion The study indicated that knowledge of women toward the legalization of abortion was low but more than half of respondents prefer abortion on demand to be legalized.